2017
DOI: 10.1177/0025817217729332
|View full text |Cite
|
Sign up to set email alerts
|

Traits of vulnerability in repetitive sexual assaults of mentally disabled people

Abstract: The issue of sexual abuse, assault, rape and unwanted pregnancies among mentally disabled women is largely under-reported for many reasons. Several myths prevail including that mentally disabled women offer little interest to sexual predators, together with a negative public attitude and this contributes to the problem. We report the case of a single centre in Albania, where repetitive sexual assaults were perpetrated against three mentally disabled women. Three unwanted pregnancies followed. The issue gained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…If researchers focus on older adults or people with a disability, the item asking about unwanted touching during care should be included. Research has namely shown that sexual victimization is prevalent within this population (Basile et al, 2016;Nobels et al, 2018;Shaqiri et al, 2018). Yet risks factors and prevalence rates of sexual neglect among older adults remain unknown (Nobels et al, 2020).…”
Section: Conclusion and Recommendations For Future Researchersmentioning
confidence: 94%
See 1 more Smart Citation
“…If researchers focus on older adults or people with a disability, the item asking about unwanted touching during care should be included. Research has namely shown that sexual victimization is prevalent within this population (Basile et al, 2016;Nobels et al, 2018;Shaqiri et al, 2018). Yet risks factors and prevalence rates of sexual neglect among older adults remain unknown (Nobels et al, 2020).…”
Section: Conclusion and Recommendations For Future Researchersmentioning
confidence: 94%
“…Other aspects of sexual neglect include not treating people as sexual beings (item 5) and disrespect of sexual intimacy (e.g., touching during care; item 7). This is particularly relevant for older adults who are often considered as people without any sexual needs (Kessel, 2001;Nobels et al, 2020; but also among people who need care due to a disability (Basile et al, 2016;Shaqiri et al, 2018). Additionally, not explaining the sexual side-effects of a treatment (item 6) can be considered as a form of denying one's sexual needs.…”
Section: Missing Itemsmentioning
confidence: 99%